The Role of Peritoneal Alternatively Activated Macrophages in the Process of Peritoneal Fibrosis Related to Peritoneal Dialysis - Wang, Jie (Molecular Diversity Preservation International (MDPI), 2013)
It has been confirmed that alternatively activated macrophages (M2) participate in tissue remodeling and fibrosis occurrence, but the effect of M2 on peritoneal fibrosis related to peritoneal dialysis (PD) hasn’t been elucidated. This study was therefore conducted to assess the association between M2 and peritoneal fibrosis related to PD. In this study, peritoneal fibrosis was induced by intraperitoneal (i.p.) injection of Lactate-4.25% dialysate (100 mL/kg) to C57BL/6J mice for 28 days, and liposome-encapsulated clodronate (LC, the specific scavenger of macrophages) was used to treat the peritoneal fibrosis mice model by i.p. injection at day 18 and day 21. All animals were sacrificed at day 29. Parietal peritonea were stained with Masson’s trichrome, and the expression of type I collagen (Col-I), fibronectin, mannose receptor (CD206), transforming growth factor beta (TGF-β), chemokine receptor 7 (CCR7), chitinase 3-like 3 (Ym-1) and arginase-1 (Arg-1) was determined by Western blotting, immunofluorescence and quantitative real-time PCR. Our results revealed that peritoneal thickness, Col-I, fibronectin, CD206, TGF-β, Ym-1 and Arg-1 were upregulated in the peritoneal fibrosis mice model, and all of these indexes were downregulated in those treated with LC. Additionally, there was no difference in the level of CCR7 between the model and treatment group. Our study indicated that peritoneal M2 played an important role in the process of peritoneal fibrosis related to PD and might be a potential target for intervention therapy of peritoneal fibrosis.